The Image of a Siren in Armenian Miniature Painting - Aperyan, Anahit (History and Culture, 2023)
Medieval miniaturists did not create random figures to illustrate manuscripts. Each of them had their own role and interpretation, and among those characters are also the sirens, about which there are few studies. In our work we studied 45 sirens images (in shrines, headdresses, lordly scenes) and after analyzing a few of them we came to the following conclusions։ In the pre-Christian period, sirens with the meaning of demons, monsters, evil spirits, which are mentioned in mythological legends, acquire a completely new meaning in the Christian period. Sirens were known for their sweet and enchanting sound. It is likely that if before the adoption of Christianity they used their enchanting voice to capture and kill people, then in the Christian period they announced Christian events with their enchanting voice. Many examples testify to that. In the Christian period, sirens announced the coming of Christ and opened the way for people to the Christian faith. So we can say that sirens are revealed as demons possessed by evil spirits in the pre-Christian period, which in the Middle Ages become harbingers of Christian realities.
Keywords: Gospel; Armenian miniature; mythical creature; siren; devil; harbinger; ornament